Response of long melon to spacing and pruning methods under insect proof net house during off-season - SINGH, AWANI KUMAR; DHAR, SHRI; SABER, NAVED; PATEL, NEELAM; SINGH, VEERPAL; SINGH, AJEET; KUMAR, ANIL (The Indian Journal of Agricultural Sciences, 2021)
The demand of long melon (Kakari-Cucumis melon var. utilissimus Duthic & Fuller) fruits during off-season are quite high in towns and cities. The off season cultivation of long melon in open field is not remunerative due to heavy losses to crop caused by infestation of insect-pest, birds and wild animals. Insect proof net house structures are suitable options to grow off-season long melon crop for high yield and good returns. An experiment was conducted under insect proof net house at CPCT, IARI, New Delhi, during off-season (August-November) 2016-17 for growing long melon var. Chitralekha with five plant spacings and five branch pruning methods. Plant spacing and pruning methods revealed significant positive influence on yield and net return. Fruit yield decreased with increasing plant spacing and it was found maximum in closer spacing of 50 cm × 20 cm. Net return and B:C ratio also followed similar trend. Amongst pruning methods, node branch pruning method (P3) gave highest yield (67.96 q/1000 m2) with maximum net return of ₹ 78391/1000 m2 and BC ratio 1:1.40 compared to other pruning intensity or no pruning (control). Three node branches pruning method was close to two node branch pruning method in total yield, net return and BC ratio. Study showed that off season cultivation of long melon under insect proof net house protected structure is a good option to farmers for generating more income and employment.